Gas-phase thermal explosions in catalytic direct oxidation of alkenes. (May 2020) - Pio, G.; Salzano, E.
Abstract: The metal-based catalytic oxidation of alkenes to the corresponding epoxides is playing a significant role in the modern chemical industry. Nevertheless, these key processes are still lacking proper understanding with respect to the gas-phase runaway behaviour (thermal explosion) and to the hot spot formation on the catalytic surface, under the typical process conditions. This work aims to enlighten these aspects by considering either the catalytic or the gas-phase chemistry for the development of reactor operative diagrams, in order to define the best-operating conditions with respect to the selectivity, the productivity, and the process safety aspects. The proposed methodology has been applied to the oxidation of ethylene and propylene for the direct oxidation process by pure oxygen, considering a detailed kinetic model accounting for the homogeneous reactions, coupled with the heterogeneous catalytic mechanisms. Sensitivity and reaction path analyses were performed to individuate the ruling species and reactions determining the transition to runaway conditions. Highlights: Development of comprehensive kinetic mechanism suitable for partial oxidation. Implementation of detailed kinetic mechanism for reactor operative diagrams production. Estimation of flammability limits under reactor relevant conditions. Individuation of preferred reaction paths governing runaways.